An Analytical Approach for Buckling of FG Cylindrical Nanopanels Resting on Pasternak’s Foundations in the Thermal Environment (Advances in Applied Mathematics and Mechanics, 2024)
In this article, the effects of temperature and size-dependent on the bucklingbehavior of functionally graded (FG) cylindrical nanopanels resting on elastic foundation using nonlocal strain gradient theory are investigated in detail analytical approach. According to a simple power-law distribution, the material properties of FGcylindrical nanopanels are assumed to vary continuously through the thickness direction. The Pasternak model is used to describe the reaction of the elastic foundation onthe FG cylindrical nanopanels. The fundamental relations and stability equations arederived by applying the nonlocal strain gradient theory and the classical shell theorybased on the adjacent equilibrium criterion. Using Galerkin’s method, the mechanicalbuckling behavior of FG cylindrical nanopanels resting on an elastic foundation in thethermal environment is solved. The reliability of the obtained results has been verified by comparison with the previous results in the literature. Based on the obtainedresults, the influences of the material length scale parameter, the nonlocal parameter,temperature increment, geometric parameters, material properties, and elastic foundation on buckling behaviors of FG cylindrical nanopanels resting on an elastic foundation in the thermal environment are analyzed and discussed.